Studi Literatur Uji Aktivitas Antioksidan pada Ekstrak Bunga Telang (Clitoria ternatea L.) dengan Berbagai Metode Pengujian - Ingka Mardiana Putri; Taufik Muhammad Fakih; Farendina Suarantika (UNISBA Press, 2024)
Abstract. Telang flower (Clitoria ternatea L.) is one plant with a source of antioxidants. Test antioxidant activity with test methods on eagle flowers is very diverse so that the levels of antioxidants can inhibit free radicals. This literature study aims to determine the extraction method with the type of solvent that can be used to test the level of antioxidant activity in telang flower extract. To determine the level of antioxidant activity of striped flower extract with test methods and to determine the content of phenol compounds that act as antioxidants in striped flower extract. This study used the method of literature study of structured article review. Data collection was conducted using Google Scholar, Science Direct and Pubmed databases with the keywords